Entrepreneurship ETR 300 Walinong Sari Enterprise / Suwaibah Aziz … [et al.] - Aziz, Suwaibah; Ketit, Helen; Najib, Naziah; Nasrudin, Syahril Annuar; Mohd Isa, Mohd Redzuan (2003)
Walinong Sari Enterprise is unlike another company partners which provided Bridal and Catering to customers. We choose the name of 'Walinong Sari' is because this name have a value. This can encourage and attract interest to peoples to use these services. Nowadays, many people prefer to choose traditional concept rather than the modem one. Located at No 21 A, Man Tengku Ampuan Zabedah, E9/E Section 9 Shah Alam and nearby the residential areas which were crowded with high- class people was one of the advantages. Thus, there have a lot of facilities provided which can help and increase our company improvements. Walinong Sari Enterprise also provided studio photographing not only for Wedding but for another function such as for graduations and commercial. Peoples of all ages and backgrounds will come to enjoy the services